Mary Queen of Scots: an illustrated life - Doran, Susan (British Library, 2007)
Tells the dramatic story of Mary's life. This work is illustrated with many of the documents, as well as pictures of the leading characters in the story. Contemporary records are either transcribed or explained with captions.